FEATURES OF CLINICAL DISPLAYS OF THE TRANSPLANTED HEART ACUTE REJECTION - S. J. Shemakin; A. J. Kormer; T. A. Khalilulin; V. V. Chestuhin; I. M. Iljinsky; A. G. Kuprijanova (Вестник трансплантологии и искусственных органов)
In the present research features of current of clinical and structural changes are considered at acute rejection at the patients who have carried orthotopic transplantation of heart. Results of retrospective research are based on studying 1119 endomyocardial biopsy in a combination to clinical displays, given invasive and the noninvasive techniques of diagnostics used at 62 recipients of heart recipients before 10-years period of supervision. Character of changes of wall thicknes of LV, mass of a myocardium, ventricular end diastolic volume, and also a degree of infringement of pump function allow to characterize distinctions in clinical displays acute cellular and humoral rejection.